Public Goods Games and Psychological Utility: Theory and Evidence - Sanjit Dhami; Mengxing Wei; Ali al-Nowaihi (Center for Economic Studies and ifo Institute (CESifo), 2018)
We consider a theoretical model of a public goods game that incorporates reciprocity, guilt-aversion/surprise-seeking, and the attribution of intentions behind these emotions. In order to test our predictions, we implement the `induced beliefs method' and a within-subjects design, using the strategy method. We find that all our psychological variables contribute towards the explanation of contributions. Guilt-aversion is pervasive at the individual-level and the aggregate-level and it is relatively more important than surprise-seeking. Our between-subjects analysis confirms the results of the within-subjects design.
Keywords: D01; D03; H41; 330; public goods games; psychological game theory; reciprocity; surprise-seeking/guilt-aversion; attribution of intentions; induced beliefs method; within and between subjects designs